2014
DOI: 10.2298/tsci121225062z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of effects of the intermediates and initial conditions on flame propagation in a real homogeneous charge compression ignition engine

Abstract: The premixed flame speed under a small four stock homogeneous charge compression ignition engine fueled with dimethyl ether was investigated. The effects of intermediate species, initial temperature, initial pressure, exhaust gas re-circulation, and equivalence ratio were studied compared to the baseline condition. Results show that under all conditions, the flame speeds calculated without intermediates are larger than those considered the intermediates. Flame speeds increase with the increase of crank angle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Results showed that the equivalence ratio and inlet pressure were the most effective parameters on the combustion phasing and performance of the engine. Zhang et al [14] studied the premixed flame speed in a dimethyl ether fueled HCCI engine. They concluded that the flame speed tends to increase with the increase of crank angle and the increment rate is higher at cool flame.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the equivalence ratio and inlet pressure were the most effective parameters on the combustion phasing and performance of the engine. Zhang et al [14] studied the premixed flame speed in a dimethyl ether fueled HCCI engine. They concluded that the flame speed tends to increase with the increase of crank angle and the increment rate is higher at cool flame.…”
Section: Introductionmentioning
confidence: 99%